Case for diagnosis - Alejandro Molina-Leyva; Santiago Perez-Parra; Federico Garcia-Garcia (Sociedade Brasileira de Dermatologia, 2014)
Majocchi's granuloma is a persistent supurative folliculitis, associated with a deep granulomatous reaction induced by dermatophytes. There are two clinical forms of Majocchi's granuloma: the superficial form that appears in healthy individuals after localized trauma; and the nodular form, which occurs in inmunocompromised patients. We present a case of nodular Majocchi's granuloma on the forearm of an immunocompetent patient. Microbiological culture and examination of a deep aspiration sample identified Trichophyton rubrum. Collecting a deep sample of tissue is essential in achieving a good diagnostic performance.